Application of a recombinant laccase-chlorogenic acid system in protein crosslink and antioxidant properties of the curd. (April 2018) - Loi, M.; Quintieri, L.; Fanelli, F.; Caputo, L.; Mulè, G.
Abstract: Milk protein crosslink through the action of enzymes represents a feasible strategy to impart new functionalities to cheese. In this work we reported the effects of a laccase mediator system (LMS) on protein crosslink and antioxidant property of curd. The crosslinking activity of a purified recombinant laccase Ery4 and a commercial enzyme preparation (cLC), with three mediators was firstly evaluated in milk and then applied before curd manufacture. Only Ery4-LMS significantly increased curd weight compared to that of the control sample. SDS-PAGE revealed that similar high molecular weight bands produced by both LMSs in milk were also retained in curds. The antioxidant activity recorded in curds with Ery4-LMS was the highest among all samples both before and after gastro-pancreatic digestion. This is the first time that a CGA-based LMS is used in manufacture of curd with improved antioxidant properties. These results open new perspectives for dairy applications. Graphical abstract: Unlabelled Image Highlights: 3 Laccase-Mediator Systems were evaluated to obtain proteins crosslink in milk. Laccase and chlorogenic acid promoted noticeable proteins crosslink after 1 h of reaction. Curds obtained after laccase-mediator treatment showed increased dry matter. Increased antioxidant properties were registered in laccase mediator treated samples after simulated digestion.